1997
DOI: 10.1590/s0100-879x1997000600008
|View full text |Cite
|
Sign up to set email alerts
|

Clastogenic effects of different Ureaplasma urealyticum serovars on human chromosomes

Abstract: The possibility that Ureaplasma urealyticum might play an important role in human infertility was first raised more than 20 years ago, but this association remains speculative. Considering the hypothesis that the pathogenicity of Ureaplasma urealyticum may depend on its serotypes, the clastogenic effects of different strains of Ureaplasma urealyticum, at concentrations of 10 3 CCU (color changing units)/ml, 10 4 CCU/ml and 10 5 CCU/ml, were evaluated in vitro in short-term cultures of human lymphocytes. Total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
1
2
0
2
Order By: Relevance
“…This effect was observed after a short infection time (30 min). These results confirm the observation that U. urealyticum causes mitotic alteration, especially chromatid gaps and chromatid breaks, in cultures of human lymphocytes [42,43].…”
Section: Discussionsupporting
confidence: 90%
“…This effect was observed after a short infection time (30 min). These results confirm the observation that U. urealyticum causes mitotic alteration, especially chromatid gaps and chromatid breaks, in cultures of human lymphocytes [42,43].…”
Section: Discussionsupporting
confidence: 90%
“…However, Reichart et al [16] concluded that U. urealyticum has a direct deleterious effect on the DNA and nuclear chromatin of human and ram spermatozoid. According to Cunha et al [20], U. urealyticum resulted in clastogenic effects on human chromosomes and on the mitotic process itself, and the clastogenic effects varied with the U. urealyticum serotypes evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Transmission of U. urealyticum to the fetus or newborn may cause severe broncopulmonar displasias, and even central nervous system (CNS) infections 1,6 . However, a difference of pathogenicity among it's 14 serotypes has been reported, by frequency of isolation from different clinical manifestations, as well as different in vitro properties 4 .…”
Section: Introductionmentioning
confidence: 99%